The Effect of Fish Oil Supplement on Serum Antioxidant Level in Patient with Rheumatoid Arthritis - Sousan Kolahi; Amir Ghorbanihaghjo; Ali-Reza Khabbazi; Mehrzad Hajialilo; Hale Farzin (Journal of Pharmacy and Nutrition Sciences, 2013)
Purpose:Rheumatoid arthritis (RA) is a common autoimmune disease characterized by inflammation and over-growth of the synovium. RA is accompanied with increased levels of free radical and stress oxidative. In recent years, there has been an increasing interest in nutritional factors on disease and autoimmune system. More recently literatures have emerged that offers contradictory findings about fish oil on antioxidant levels. So far however, there has been little discussion about fish oil as antioxidant on Rheumatoid arthritis. This paper will focus on effect of fish oil over serum antioxidant levels and activity disease of RA. Methods: A randomized double blinded control trial 90 patients from a population of Rheumatoid Arthritis who were selected. Forty five patients received Fish oil (FO) (1gr /day) in addition of conventional therapy for RA versus 45 patients received placebo. And serum levels of plasma antioxidant capacity (TAC) and the activity of superoxide dismutase (SOD) and Glutathione peroxides (GPX) were measured. Results:There was no statistically difference between groups in plasma antioxidant capacity and the activity of superoxide dismutase, Glutathione peroxides. There weren’t any correlation among DAS and antioxidant serum levels. Conclusion: The findings emerging from the present inquiry suggested that FO with 1 gram daily dose didn’t have effect on serum antioxidant level and activity of disease in RA.